The Effectiveness Quality Of Information Systems And City Walk Concepts Toward City Branding - Sari Wiyanti (Institute of Computer Science (IOCS), 2022)
This research is conducted in Indonesia, precisely in Tegal City as an object that is currently increasing its regional competitiveness. Tegal City is a small city located on the north coast as an autonomous region with limited natural resources. The efforts made by Tegal city government to become a city branding to compete with the surrounding area are a formidable challenge. The local government of Tegal City which already has a branding with the distinctive language of the Ngapak-ngapak Tegalan and favors tourism on the north coast. Quality and reliable Information System Technology is easily accessible by the people of Tegal City and other areas, as well as the governance of Tegal City as a destination as an important variable to be researched. The sample used in this study was 100 users of Tegal city government information system and visitors to Tegal city walk who were determined by random sampling. The sampling technique used was accidental sampling by determining the characteristics according to the purpose of this study. Data collection techniques used in this study by providing a questionnaire containing written questions to be answered by respondents. The data from the questionnaire will be analyzed using multiple linear regression analysis techniques with the help of the SPSS 25 program. The results of the study show the effect of the effectiveness of Information System Quality and City Walk Concept in building of Tegal City as City Branding.